ASSESSING THE IMPACT OF ACIDIC DRINKS ON THE STRUCTURAL INTEGRITY OF ENAMEL AND THEIR CONSEQUENCES FOR DENTAL AESTHETICS - Berivan Laura Rebeca Buzatu; Roxana Buzatu; Atena Galuscan; Delia Abrudan Luca; Ruxandra Sava Rosianu; Octavia Balean; Titus Vlase; Daniela Jumanca (Romanian Journal of Oral Rehabilitation)
Aim of the study: This study seeks to evaluate the detrimental effects of acidic beverages on tooth structure and overall dental health, with a particular focus on comparing the extent of damage at a microscopic level. While it is widely understood that acidic drinks are harmful to teeth, the precise scale of the damage is often underestimated. By examining the degree of harm caused by prolonged exposure to acidic substances, this research aims to increase awareness of the cumulative effects that sugary and acidic beverages have on dental health and aesthetics over time. Materials and methods: The teeth used in this study were obtained from private practice, from patients diagnosed with Stage 3 or 4 periodontitis. These teeth were deemed unsuitable for prosthetic treatment due to excessive clinical attachment loss (CAL) or advanced tooth mobility (grade 2 or 3). Following extraction, the teeth were preserved in artificial saliva for a maximum of 20 days.The experiment involved a sample of 30 teeth, each of which was submerged in a different beverage for a duration of 24 hours The beverages used in this study were Sprite, lime juice, apple vinegar, and white wine. Following the 24-hour exposure, the teeth were documented, and photographs were taken. The enamel surface of the teeth was then analyzed under a Scanning Electron Microscope (SEM) to examine the extent of acid-induced damage in detail. Additionally, the density of the two halves of each tooth was compared using a Diagnodent pen (KaVo) to further assess the impact of the acidic beverages. Results: The results of this study will contribute to a deeper understanding of enamel erosion caused by acidic beverages, offering valuable insights for both dental professionals and individuals aiming to protect their enamel from deterioration. Conclusions: In conclusion, the excessive and frequent consumption of acidic beverages results in irreversible enamel demineralization, leading to aesthetic concerns such as white spots, discoloration, surface roughness, and an increased risk of tooth sensitivity or loss. Additionally, the method of consumption—particularly the tendency to a prolonged the contact between these beverages and the dental structure—exacerbates the potential for damage. To minimize these effects, it is imperative to reduce both the frequency of acidic drink intake and the duration of their contact with the teeth. Effective management of acidic beverage consumption is essential for preserving oral health and maintaining dental aesthetics.